Effect of repeated sessions of dual-site anodal tDCS on post-exercise performance and subjective recovery in recreationally active females: a randomized controlled trial - Melahbid, Shima Sharifi; Amiri, Ehsan; Tadibi, Vahid; Machado, Daniel Gomes da Silva (Frontiers in Physiology, 2025)
BackgroundPrevious studies have investigated the effects of transcranial direct current stimulation (tDCS) on performance enhancement, but limited research has examined its impact on post-exercise recovery. This study aimed to assess the effects of three consecutive sessions of dual-site anodal tDCS, targeting the primary motor cortex (M1) and the left dorsolateral prefrontal cortex (L-DLPFC), on both subjective and objective recovery measures in recreationally active females.MethodsTwenty-five recreationally active females were randomly assigned to either an anodal tDCS group (n = 13) or a sham group (n = 12). Performance and recovery were assessed at three time points: (1) before tDCS intervention, (2) immediately after a fatigue-inducing time-to-exhaustion test, and (3) following a 24-h recovery period. Participants completed a 3-km cycling time trial (TT) and a Sargent Jump Test (SJT) at each assessment. Additionally, after 24 h of recovery, they completed the Total Quality Recovery (TQR) scale and the Wellbeing Questionnaire (WBQ). Following baseline measurements, participants received their assigned intervention, three consecutive daily stimulation sessions (2 mA, 20 min, targeting + F3/-AF8 and +Cz/-AFz simultaneously), before the fatigue-inducing task.ResultsBoth groups exhibited similar physiological and perceived exertion responses during the fatigue-inducing task (all p > 0.05). While the a-tDCS group showed significant improvements in 3-km TT performance at 24 h post-recovery compared to baseline (p < 0.001, 95% CI [-36.71, −11.33]) and post-fatigue (p < 0.001, 95% CI [-28.4, −8.96]), there were no between-group differences (p > 0.05). However, the tDCS group reported higher TQR scores than the sham group at 24 h (p = 0.046, 95% CI [0.000, 2.000]). No significant between-group differences were observed in explosive performance (SJT) or WBQ scores (all p > 0.05).ConclusionThree sessions of dual-site a-tDCS targeting M1 and L-DLPFC may enhance perceived recovery (TQR) in recreationally active females, but do not significantly influence wellbeing (WBQ) or objective performance recovery measures. The benefit appears to be subjective only, without a measurable performance advantage.Clinical trial registrationThe trial was registered in the Iranian Clinical Trial Registry (www.irct.behdasht.gov.ir, IRCT ID: IRCT20230925059509N1).